Bonding, bridging and linking relationships of the CSR target communities of PT Pertamina Refinery Unit II Sungai Pakning - Widhagdha, Miftah Faridl; Wahyuni, Hermin Indah; Sulhan, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2019)
PT Pertamina (Persero) Sungai Pakning Refinery Unit II as one of Indonesia's state-owned oil and gas companies has contributed to the empowerment of communities around its operational areas through the Corporate Social Responsibility (CSR) scheme. In carrying out CSR programs, the company pays attention to the social relations of the target communities. This study focuses on analyzing the forms of social relations of the CSR target communities and their impacts on the implementation of CSR programs of PT Pertamina (Persero) Refinery Unit II Sungai Pakning. Social relations in this study are defined into three forms of relations, namely bonding, bridging and linking, each of which has different impacts on the social conditions of the beneficiary communities. This research is based on qualitative approach, conducted in three target communities in different areas within Bengkalis Regency, Riau Province, namely Sungai Pakning Village, Sungai Selari Village, and Pangkalan Jambi Village, during the period of 2017-2018. The data were collected through in-depth interviews, observations, and documentations. The study finds various forms of social relations. Bonding relations show that intra-group bonds are important to maintain group cohesiveness. Bridging relations show that ties between groups need to be developed in order to connect each others and work together. While the linking relationships show that there is a good impact for groups that have closer relationships with the higher power institutions. These results indicate that the forms of social relations have important impacts on the implementation of CSR programs and need to be maintained through participatory communication activities in order to create sustainable social relations. This study also finds that good social relations will be strong support to raise community awareness and participation in practicing sustainable environmental management.